Renovation and modernization of residential structures in Gliwice based on survey of the environment built from the years 1848-2014 = Renowacja i modernizacja struktury mieszkaniowej w Gliwicach na podstawie badań ankietowych środowiska zbudowanego z lat 1848-2014 - Cibis, Jerzy; Serdyńska, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the survey carried out in 2013-2014 are changes in Gliwice residential substance in relation to the two fundamental issues: how proceeded transformation of the existing housing stock, which changes has it undergone during operation. The range of changes within the housing illustrates all the positive and negative solutions characteristic for each of the periods.
Keywords: zasoby mieszkaniowe; Górny Śląsk; modernizacja; renowacja; ankieta; housing resources; Upper Silesia; modernisation; renovation; survey